Increase in tracheal investment with beetle size supports hypothesis of oxygen limitation on insect gigantism - Kaiser, Alexander (National Academy of Sciences, 2007)
Recent studies have suggested that Paleozoic hyperoxia enabled animal gigantism, and the subsequent hypoxia drove a reduction in animal size. This evolutionary hypothesis depends on the argument that gas exchange in many invertebrates and skin-breathing vertebrates becomes compromised at large sizes because of distance effects on diffusion. In contrast to vertebrates, which use respiratory and circulatory systems in series, gas exchange in insects is almost exclusively determined by the tracheal system, providing a particularly suitable model to investigate possible limitations of oxygen delivery on size. In this study, we used synchrotron x-ray phase–contrast imaging to visualize the tracheal system and quantify its dimensions in four species of darkling beetles varying in mass by 3 orders of magnitude. We document that, in striking contrast to the pattern observed in vertebrates, larger insects devote a greater fraction of their body to the respiratory system, as tracheal volume scaled with mass(1.29). The trend is greatest in the legs; the cross-sectional area of the trachea penetrating the leg orifice scaled with mass(1.02), whereas the cross-sectional area of the leg orifice scaled with mass(0.77). These trends suggest the space available for tracheae within the leg may ultimately limit the maximum size of extant beetles. Because the size of the tracheal system can be reduced when oxygen supply is increased, hyperoxia, as occurred during late Carboniferous and early Permian, may have facilitated the evolution of giant insects by allowing limbs to reach larger sizes before the tracheal system became limited by spatial constraints.